Caracterização das emissões gasosas provenientes da queima de biomassa de bagaço de cana de açúcar - Tempesta, Henrique Novaes [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Faced with increasingly frequent natural disasters, and a future that is not encouraging in relation to the environmental problems that the planet will suffer in the near future, people, governments and companies are beginning to rethink their roles in society. One of the ways to reduce the effect of global warming is through the use of biomass as fuel in combustion processes, replacing petroleum derivatives. In Brazil, the most prominent biomass for this use is sugarcane bagasse, derived from the sugar-alcohol industry. However, several aspects of a fuel must be evaluated to determine whether its use is environmentally viable, such as determining pollutant emissions from the combustion process. This work aimed to determine the concentration of CO, CO2, NO2, NOx, SO2 formed in this process and to evaluate the control of these pollutants. Sampling took place in a burner equipped with a scrubber Venturi, an equipment used industrially to reduce the amount of pollutants emitted into the atmosphere. A gas sampler was positioned in the chimney of the burner, making it possible to carry out the experiments. The concentration results were between 19 and 20% for CO2, 44.40 and 256.98 ppm for CO, 0.97 and 3.44 for NO2, 3.44 to 32.48 ppm for NOx and 0 to 3.14 ppm for SO2. This study proves to be relevant in order to enrich the literature on the subject, in addition to serving as inspiration for new studies and encouraging the use of this biomass as an energy source. Finally, the results were close to another research carried out with bagasse, and smaller than most similar projects carried out with other raw materials, in addition, emissions were within the limits established by current legislation.

Diante de catástrofes naturais cada vez mais frequentes, e um futuro nada animador em relação aos problemas ambientais que o planeta irá sofrer no futuro próximo, as pessoas, governos e empresas começam a repensar seus papeis na sociedade. Uma das formas de se diminuir o efeito do aquecimento global, é por meio da utilização de biomassas como combustível em processos de combustão, substituindo os derivados de petróleo. No Brasil, a biomassa mais proeminente para esse uso é o bagaço de cana de açúcar, derivado da indústria sucroalcooleira. No entanto deve-se avaliar vários aspectos de um combustível para determinar se seu uso é viável ambientalmente, como determinar as emissões de poluentes decorrente do processo de combustão. Este trabalho teve como objetivo determinar a concentração de CO, CO2, NO2, NOx, SO2 formados nesse processo e avaliar o controle destes poluentes. A amostragem se deu em um queimador dotado de um lavador Venturi, um equipamento usado industrialmente para diminuir a quantidade de poluentes emitidos para a atmosfera. Um amostrador de gás foi posicionado na chaminé do queimador, possibilitando realizar os experimentos. Os resultados concentrações foram entre 19 e 20% para o CO2, 44,40 e 256,98 ppm para o CO, 0,97 e 3,44 para o NO2, 3,44 até 32,48 ppm para o NOx e 0 até 3,14 ppm para o SO2. Esse estudo se mostra relevante de forma a enriquecer a literatura sobre o tema, além de servir como inspiração para novos estudos e incentivar o uso dessa biomassa como fonte de energia. Por fim, os resultados se mostraram próximos a outra pesquisa realizado com bagaço, e menores que a maioria dos projetos semelhantes realizados com outras matérias primas, além disso as emissões ficaram dentro dos limites estabelecidos pela legislação vigente.
Characterization of gas emissions from the burning of sugarcane bagasse biomass
Keywords: Bagasse; Biomass; Venturi washer; Bagaço; Biomassa; Lavador Venturi